2021
DOI: 10.3390/ijerph18073400
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Suicide Stigma and Associated Factors in Chinese College Students: Translation and Validation of the Stigma of Suicide Attempt Scale and the Stigma of Suicide and Suicide Survivors Scale

Abstract: This study aims to translate and validate two perceived suicide stigma scales, including the Stigma of Suicide Attempt Scale (STOSA) and the Stigma of Suicide and Suicide Survivor Scale (STOSASS) into Chinese language, examining the factor structure, and assessing the correlation between suicide stigma and a series of variables. After translating and back translating the STOSA and STOSASS, an online survey was administrated to 412 college students in China. These two scales were tested for their dimensionality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 75 publications
0
6
0
Order By: Relevance
“…The results showed strong correlations among these variables and suggested that there was a lack of education on the topic of suicide in Chinese colleges. In a study assessing stigma toward suicide, suicide attempts, and suicide survival in a student sample, Wu and colleagues revealed positive correlations between suicidality, suicide exposure, and endorsement of suicide [66]. However, these studies mainly focused on scale development and translation and did not explore suicide attempts.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed strong correlations among these variables and suggested that there was a lack of education on the topic of suicide in Chinese colleges. In a study assessing stigma toward suicide, suicide attempts, and suicide survival in a student sample, Wu and colleagues revealed positive correlations between suicidality, suicide exposure, and endorsement of suicide [66]. However, these studies mainly focused on scale development and translation and did not explore suicide attempts.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in comparison to Chinese university students (Han et al, 2017(Han et al, , 2018Wu et al, 2021) who were surveyed with the same instrument, Chinese Indonesians in this study showed relatively lower levels of stigmatization. This result might be associated with their ethnic minority status in the country that enabled them to be more sympathetic toward adversity.…”
Section: Discussionmentioning
confidence: 67%
“…As the finding is in line with previous findings in Australia (Batterham et al, 2013) and China (Han et al, 2017), this indicates that there is a cross-cultural universal pattern between suicidal ideation and glorification of suicide. Another explanation might come from the role of specific Chinese cultural interpretation toward suicide, as it is historically interpreted as an effort to restore the person’s (or family’s) honor or advocate for justice in Chinese culture (Wu et al, 2021). Hence, those with suicidal ideation would have a cultural narrative that fits with their ideation as something heroic compared to those who do not have any suicidal ideation.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in comparison to Chinese university students (Han et al, 2018;Han et al, 2017;Wu et al, 2021) and Lao communities (Yang et al, 2018) who were surveyed with the same instrument, Chinese Indonesians in this study showed relatively lower levels of stigmatization. This result might be associated with their ethnic-minority status in the country that enabled them to be more sympathetic towards adversity.…”
Section: Discussionmentioning
confidence: 69%
“…This finding is in line with previous findings in Australia (Batterham et al, 2013) and China (Han et al, 2017) which might indicate that there is a cross-cultural universal pattern between suicidal ideation and glorification of suicide. However, there might also be a specific Chinese cultural role as suicide is historically interpreted as an effort to restore the person's (or family's) honor or advocate for justice in Chinese culture (Wu et al, 2021). Hence, those with suicidal ideation would have a cultural narrative that fits with their ideation as something heroic compared to those who do not have any suicidal ideation.…”
Section: Discussionmentioning
confidence: 99%